Re-irradiation of recurrent vertebral metastasis after two previous spinal cord irradiation: A case report - Bentahila, Rita; Kinj, Rémy; Huck, Constance; El Houat, Yasmine; Mampuya, Ange; Tuleasca, Constantin; Ozsahin, Mahmut; Bourhis, Jean; Schiappacasse, Luis (Frontiers in Oncology, 2023)
Background Management of a recurrent vertebral metastasis in a situation of previously irradiated spinal cord is a challenging clinical dilemma. Case presentation We report a first case of second retreatment of a spinal metastasis initially irradiated with standard radiotherapy and stereotactic body radiation therapy (SBRT), who subsequently progressed with imaging-confirmed local tumor progression at the same level. After a third course of irradiation with SBRT, a complete response was achieved. After 8 months of follow-up, the patients remains free of local recurrence. Conclusion A third course of vertebral irradiation for a recurrent vertebral metastasis failing to two previous irradiations, in this particular case, have shown the feasibility and efficacy of the technique as a salvage treatment option. This approach could be used in a selected group of patient if an adequate dose is delivered to the target while observing critical tissue tolerance limits.